Validation of radio frequency treatments as alternative non-chemical methods for disinfesting chestnuts. (July 2015) - Hou, Lixia; Hou, Juncai; Li, Zhongxin; Johnson, Judy A.; Wang, Shaojin
Abstract: Chemical fumigation has been widely used to control insects in postharvest chestnuts but is inherent dangers when using fumigants. The purpose of this study was to validate application of radio frequency (RF) treatments for disinfesting chestnuts as an alternative to chemical fumigation. A practical process protocol was developed to control insect pests in chestnuts using a 27.12 MHz free-running oscillator RF system. Fifth-instar yellow peach moth, Conogethes punctiferalis, more heat tolerant than chestnut weevil, Curculio elephas, under three temperature and time combinations using a heating block system, was selected as the targeted insect to validate the RF treatment protocol. Mortality of fifth-instar C. punctiferalis increased with increasing holding time at 55 °C using RF heating and reached 100% while holding in hot air for at least 5 min. Furthermore, there was no significant quality difference in color, fat, firmness, moisture content, protein, and soluble sugar content of chestnuts observed between RF treatments and controls. RF treatment methods hold potential to scale up for industrial applications of disinfesting chestnuts. Highlights: A practical RF treatment protocol was validated for disinfesting chestnuts. Fifth-instar Conogethes punctiferalis was more heat tolerant than Curculio elephas . Mortality of fifth-instar C. punctiferalis increased with increasing holding time. RF heating to 55 °C and holding for 5 min reached 100% insect mortality. Chestnut quality was maintained after RF treatment.